Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1979181
|View full text |Cite
|
Sign up to set email alerts
|

The effects of task dimensionality, endpoint deviation, throughput calculation, and experiment design on pointing measures and models

Abstract: Fitts' law (1954) characterizes pointing speed-accuracy performance as throughput, whose invariance to target distances (A) and sizes (W) is known. However, it is unknown whether throughput and Fitts' law models in general are invariant to task dimensionality (1-D vs. 2-D), whether univariate (SD x ) or bivariate (SD x,y ) endpoint deviation is used, whether throughput is calculated using the mean-of-means approach or the slope-inverse approach, or whether Guiard's (2009) Form × Scale experiment design is used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 30 publications
(84 reference statements)
0
37
0
Order By: Relevance
“…Participants performed 1D and 2D Fitts's Law tasks, for which we used Wobbrock et al's FittsStudy tool, an ISO-9241-9-compliant C# application to "administer conditions, log data, parse files, visualize trials and calculate results" [23]. The tool was configured to administer nine different combinations of A (amplitude) × W (width) defined by three levels of A {250, 500, 1000} crossed with three levels of W {20, 60,130}, yielding nine values of ID {1.55, 2.28, 2.37, 3.12, 3.22, 3.75, 4.14, 4.7, 5.67}.…”
Section: Foot Devicementioning
confidence: 99%
“…Participants performed 1D and 2D Fitts's Law tasks, for which we used Wobbrock et al's FittsStudy tool, an ISO-9241-9-compliant C# application to "administer conditions, log data, parse files, visualize trials and calculate results" [23]. The tool was configured to administer nine different combinations of A (amplitude) × W (width) defined by three levels of A {250, 500, 1000} crossed with three levels of W {20, 60,130}, yielding nine values of ID {1.55, 2.28, 2.37, 3.12, 3.22, 3.75, 4.14, 4.7, 5.67}.…”
Section: Foot Devicementioning
confidence: 99%
“…The input device was a Logitech optical mouse. We built a full-screen program in C♯ called FittsStudy [14] to facilitate the study.…”
Section: Methods Subjects and Apparatusmentioning
confidence: 99%
“…A deviation of 1-D coordinates around a centroid reduces to the standard deviation formula for scalars. However, in 2-D, this reduction does not occur [14]; accordingly, we have the option of either using SD x and ignoring deviation orthogonal to the task axis, or of using bivariate deviation SD x,y and capturing deviation in both dimensions. For completeness, we explore error predictions using both univariate (SD x ) and bivariate (SD x,y ) endpoint deviation as the basis for W e and ID e .…”
Section: A Note On Endpoint Deviation In 2-dmentioning
confidence: 99%
See 1 more Smart Citation
“…the univariate endpoint deviation). More recently, Wobbrock et al [30] showed that this method of calculating W e for 2-D targeting tasks is less appropriate and the spread of hits around their centre of mass should be used (i.e. the bivariate endpoint deviation).…”
Section: Using Fitts' Law To Evaluate Touchscreen Gesturesmentioning
confidence: 99%